Student perceived value of engineering labs: a lab assessment instrument - Cook-Chennault, Kimberly; Farooq, Ahmad (Institute of Advanced Engineering and Science, 2024)
Traditionally, engineering labs are expected to reinforce fundamental science, technology, engineering, and mathematical concepts that students need to demonstrate learning in the discipline. The emergence of online degrees, the COVID pandemic, and the development of virtual lab technologies have advanced how educators design lab courses. As these new laboratory environments and practices emerge, the need for tools to evaluate how students experience and value these labs are needed. The Student Perceived Value of an Engineering Laboratory (SPVEL) assessment instrument was designed to address this need. SPVEL is framed on the Technology Acceptance Model, Inputs-Environment-Outcome Conceptual Model, and Engineering Role Identity model. In this work, the SPVEL is validated for in-person engineering laboratories. An Exploratory Load Factor analysis was conducted on the responses to twenty-five questionnaire items using a dataset of 208 participants. The Principal Components Method was employed to extract five factors. Cronbach’s alphas for data reliability for each factor ranged from 0.65 to 0.93, indicating high internal consistency. SPVEL provides a mechanism for elucidating students’ perception of their laboratory experiences, how these experiences influence their engineering role identities, and how students value laboratory experiences as preparatory and reflective of the skills needed for their careers in engineering.